STRATEGI PEMANFAATAN CHATBOT AI SEBAGAI TUTOR VIRTUAL UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF SISWA MENENGAH ATAS - Hidayat, Deden Taufik; Suryadi, Ahmad (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2025)
This study aims to design and evaluate a project-based learning strategy integrating Chatbot AI (ChatGPT) as a virtual tutor to enhance the creative thinking skills of senior high school students. The research is motivated by the need for more contextual, interactive learning approaches that support 21st-century skill development through the integration of artificial intelligence technology. The development process adopted the Dick and Carey instructional design model, which includes needs analysis, instructional goal formulation, material and media development, expert validation, and field testing in real classrooms. The Project-Based Learning (PjBL) strategy emphasizes authentic problem-solving, collaborative group work, product development, in-depth investigation, and reflection, with ChatGPT serving as a virtual tutor to facilitate idea exploration, prompting, concept clarification, and reflective support. Validation by education, content, and media experts placed the strategy in the Highly Feasible category with an average score of 95%, assessing content quality, language clarity, practical implementation, and media relevance. Field testing on the Fluida Statis topic showed a significant learning improvement, with average pretest scores of 53.08 and posttest scores of 82.28, resulting in an N-Gain of 0.62 (Medium–High category). Product assessments by teachers using a creativity rubric yielded average scores above 85 across all groups (Highly Good category). Observations of student activities during implementation recorded an average score of 3.74 on a 1–4 scale, equivalent to 93.5%, also categorized as Highly Good, indicating active engagement, curiosity, strategic use of AI, collaboration, and reflective ability. The study concludes that this project-based learning strategy supported by Chatbot AI (ChatGPT) is theoretically valid, practically feasible, and empirically effective in enhancing the creative thinking skills of senior high school students. It supports the implementation of contextual problem-based learning, the integration of AI technology in education, and the development of 21st-century skills in alignment with national curriculum policies.